Mitigation of seismic waves: Metabarriers and metafoundations bench tested. (27th October 2020) - Colombi, Andrea; Zaccherini, Rachele; Aguzzi, Giulia; Palermo, Antonio; Chatzi, Eleni
Abstract: The article analyses two potential metamaterial designs, the metafoundation and the metabarrier, capable to attenuate seismic waves impact on buildings or structural components in a frequency band between 3.5 and 8 Hz. The metafoundation serves the dual purpose of reducing the seismic response and supporting the superstructure. Conversely the metabarrier surrounds and shields the structure from incoming waves. The two solutions are based on a cell layout of local resonators whose dynamic properties are tuned using finite element simulations combined with Bloch periodicity boundary conditions. To enlarge the attenuation band, a graded design where the resonant frequency of each cell varies spatially is employed. If appropriately enlarged or reduced, the metamaterial designs could attenuate lower frequency seismic waves or groundborne vibrations respectively. A sensitivity analysis over various design parameters including size, number of resonators, soil type and source directivity, carried out by computing full 3D numerical simulations in time domain for horizontal shear waves is proposed. Overall, the metamaterial solutions discussed here can reduce the spectral amplification of the superstructure by approx. 15–70% depending on several parameters such as the metastructure size and the properties of the soil. Pitfalls and advantages of each configuration are discussed in detail. The role of damping, crucial to avoid multiple resonant coupling, and the analogies between graded metamaterials and tuned mass dampers is also investigated. Highlights: Time domain 3D simulations of metamaterials including soil, superstructure and various parameters. Metamaterial graded design strongly enlarges the mitigation bandwidth. Resonant coupling between superstructure and metamaterial leads to detuning but not amplification. Mitigation of the seismic input may range from 15% to 70% depending on soil type and metamaterial design.